Fast networking strategy of spacecraft based on competing time slots - Song Zhaohan; Zhang Dezhi (Dianzi Jishu Yingyong, 2022)
This paper mainly studies the initial networking strategy of distributed space vehicle ad hoc network without initial slot allocation and fixed time reference terminal. In view of the characteristics of space vehicle network topology, small number of nodes, temporary collaborative networking tasks and high reliability requirements, this paper proposes a competitive networking strategy based on time division multiple access(TDMA), establishes a Markov decision model, calculates the optimal competition probability, and completes the rapid establishment of the network. The simulation results show that the competitive networking strategy proposed in this paper has the characteristics of short network establishment time and high reliability, and improves the rapidity, flexibility and security of the network.